Understanding the association between admission source and in-hospital delirium: A cross-sectional study. (January 2023) - Thomas, Meghan K; Heincelman, Marc E; Zhang, Jingwen; Marsden, Justin; Dulin, Jennifer; Robbins, Patrick; Hunt, Kelly; Mauldin, Patrick; Moran, William P; Kalivas, Benjamin
Patients admitted via interhospital transfer (IHT) experience increased risk-adjusted mortality, adverse events, length of stay, and discharge to facility; however, the etiology is not well understood. We hypothesize that IHTs are more likely to experience in-hospital delirium as compared with admissions to the hospital via the emergency department (ED) and clinic. This is a cross-sectional study of all adult admissions to medical, surgical, neurological, and obstetrics and gynecology services at an academic medical center who were screened for delirium between August 2018 and January 2020. Unit of analysis was admission source (IHT vs ED vs clinic) as the independent variable and the primary outcome was in-hospital delirium, assessed with initial brief confusion assessment method (bCAM) screening. 30, 100 hospitalizations were included in this study with 3925 admissions (13.0%) screening positive for delirium at the initial bCAM assessment. The prevalence of delirium was much higher in IHTs at 22.3% (1334/5971) when compared with clinic at 5.8% (244/4214) and ED at 11.8% (2347/19, 915) admissions. Multivariable logistic regression adjusting for demographics and comorbidities showed that IHT admissions had higher odds (OR 1.91, 95% CI 1.74 to 2.10) and clinic admissions had lower odds (OR 0.56, 95% CI 0.48 to 0.64) of in-hospital delirium compared with ED admissions. Increased odds of delirium in IHT admissions may contribute to the observed increased length of stay, discharge to facility, and mortality. These results emphasize the importance of routine screening and possible intervention prior to patient transfer.